2019
DOI: 10.2147/ijn.s209773
|View full text |Cite
|
Sign up to set email alerts
|

<p>Kaempferol conjugated gold nanoclusters enabled efficient for anticancer therapeutics to A549 lung cancer cells</p>

Abstract: Background: Kaempferol (K) is a recognized anticancer drug that can conjugate with small-size gold nanoclusters (AuNCs). Materials and methods: K-AuNCs were synthesized and their use as an anticancer drug was explored using A549 lung cancer cells. Colony formation and cell migration assays were carried out. The morphology of the K-AuNCs treated A549 cells was explored using bio-atomic force microscopy. Results: The K-AuNCs were 1-3 nm in diameter and e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
32
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(38 citation statements)
references
References 31 publications
(31 reference statements)
0
32
0
1
Order By: Relevance
“…In immortalized human retinal pigment epithelial (ARPE-19) cells, treatment with kaempferol was able to decrease cell migration through ERK1/2 signaling [346]. Kaempferol-conjugated gold nanoclusters (K-AuNCs) were developed by Govindaraju et al [424] as a potential anti-cancer drug delivery system, and they demonstrated that K-AuNCs targeted A549 lung cancer cells and exhibited toxicity via nucleus damage.…”
Section: Kaempferolmentioning
confidence: 99%
“…In immortalized human retinal pigment epithelial (ARPE-19) cells, treatment with kaempferol was able to decrease cell migration through ERK1/2 signaling [346]. Kaempferol-conjugated gold nanoclusters (K-AuNCs) were developed by Govindaraju et al [424] as a potential anti-cancer drug delivery system, and they demonstrated that K-AuNCs targeted A549 lung cancer cells and exhibited toxicity via nucleus damage.…”
Section: Kaempferolmentioning
confidence: 99%
“…The potential anticancer effect of this flavonoid is associated with inhibition of phosphatidylinositol-3-kinase (Pl-3) and ribosomal s6 kinase (rsk) and cell cycle arrest in various cancer types [ 94 ]. In vitro studies have demonstrated that kaempferol nanoparticles can inhibit carcinogenesis in ovarian cancer cells (A2780/CP70 and OVCAR-3) [ 93 ], rat glioma cells (C6) [ 95 ] and lung cancer cells (A549) [ 96 ]. In the study by Luo et al both PEO-PPO-PEO as well as PLGA nanoparticles formulations incorporating kaempferol significantly reduced viability of ovarian cancer cells (A2780/CP70 and OVCAR-3), compared with kaempferol alone [ 93 ].…”
Section: Kaempferolmentioning
confidence: 99%
“…Furthermore, TnF-carrying aunPs have been indicated to be more effective against tumor cells compared with naive TnF (41). Studies have also been performed on aunPs featuring optimization of either the particle or the drug payload (42,43). dM1, which is a maytansine analogue, was developed as a microtubulin inhibitor with the same mechanism of action as paclitaxel, but its toxicity and narrow therapeutic window limited its clinical development.…”
Section: Development Of Aunps For Antineoplastic Drug Deliverymentioning
confidence: 99%
“…conjugation of dM1 with ultra-small (diameter, 2 nm) aunPs prolonged the half-life of dM1, increased its cytotoxicity in Bel7404 and HepG2 cells and also improved its tolerability and efficacy in ectopic xenograft models of hepatocellular carcinoma (42). The conjugation of kaempferol, a flavonoid that damages dna in malignant cells, to 2-nm gold nanoclusters decreases toxicity to normal cells, enhances toxicity to cancer cells and decreases proliferation, colony formation and migration of a549 lung cancer cells (43).…”
Section: Development Of Aunps For Antineoplastic Drug Deliverymentioning
confidence: 99%